Estimation of adult age‐at‐death from entheseal robusticity: A test using an identified Italian skeletal collection. Issue 1 (29th June 2020) - Milella, Marco; Belcastro, Maria Giovanna; Mariotti, Valentina; Nikita, Efthymia
Abstract: Objectives: The present study tests the effectiveness of entheseal robusticity (ER) as a potential predictor of adult age‐at‐death by applying multiple regression models to a large contemporary identified skeletal sample. Materials and Methods: ER was recorded for 23 bilateral postcranial entheses on 481 adult individuals (271 females and 210 males) from the Frassetto identified skeletal collection of Sassari (Italy), following the method of Mariotti et al. 2007. ER scores were used as predictors in multiple regression analyses with age as the dependent variable; the performance of the resulting models was tested through standard error of estimate, the correlation coefficient between predicted and documented age, and the percentage of correctly classified individuals. Results: ER show a higher correlation with age in females, resulting in more accurate estimates when compared with those obtained for males. Age‐at‐death is overestimated for male individuals under 45 years old and underestimated for older individuals. Regression models including a reduced set of ER sites result in better estimates compared with those using the complete set of variables. Discussion: Results suggest the potential usefulness of ER for the estimation of age, especially for female skeletal remains. If used with caution, ER may be a valid complement to existing methods for the reconstruction of the biological profile of skeletal remains of archaeological and forensic interest.